1969
DOI: 10.1037/h0028433
|View full text |Cite
|
Sign up to set email alerts
|

Good Samaritanism: An underground phenomenon?

Abstract: A field experiment was performed to investigate the effect of several variables on helping behavior, using the express trains of the New York 8th Avenue Independent Subway as a laboratory on wheels. Four teams of students, each one made up of a victim, model, and two observers, staged standard collapses in which type of victim (drunk or ill), race of victim (black or white) and presence or absence of a model were varied. Data recorded by observers included number and race of observers, latency of the helping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
272
7
8

Year Published

1976
1976
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(299 citation statements)
references
References 9 publications
(12 reference statements)
12
272
7
8
Order By: Relevance
“…235 Overall helping behaviour decreases with an increasing number of bystanders (the concept of diffusion of responsibility). 234,[236][237][238][239] Simple and complex behavioural methods exist to address those issues. [240][241][242] CPR teaching should include information on the concepts of ambiguity and diffusion of responsibility.…”
Section: Where Should Cpr Instructions Be Given?mentioning
confidence: 99%
“…235 Overall helping behaviour decreases with an increasing number of bystanders (the concept of diffusion of responsibility). 234,[236][237][238][239] Simple and complex behavioural methods exist to address those issues. [240][241][242] CPR teaching should include information on the concepts of ambiguity and diffusion of responsibility.…”
Section: Where Should Cpr Instructions Be Given?mentioning
confidence: 99%
“…51 Clark and Word 1972. 52 Piliavin et al 1969. For additional studies, see Clark and Word 1974, Schwartz and Gottlieb 1980, and Fischer et al 2006.…”
Section: Group Effects and Helpingmentioning
confidence: 99%
“…However, studies of actual affirming behavior itself reach the same conclusion. For example, Latane and Darley and Piliavin et al found that high proportions of people did assist researchers pretending to be in distress (Latane and Darley 1970;Piliavin et al 1969). Even in poor urban areas, where a lack of social capital or physical resources is thought to discourage altruism, a vast majority of residents reported witnessing affirming behavior including "saving the life of someone who was in danger; taking permanent custody of, or providing temporary care for, the children of neighbors; providing housing for homeless individuals and families; intervening to protect others from crime or violence; and providing money, food, clothes, guidance, and encouragement to others" (Mattis et al 2009).…”
Section: Evidence Of Affirming Behaviormentioning
confidence: 99%